Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.sbsr.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

A novel ZnO piezoelectric microcantilever energy scavenger: Fabrication and characterization

Abstract: This novel piezoelectric zinc oxide (ZnO) thin film microcantilever was fabricated by micromachining technique. To release the cantilever, wet anisotropic etching of Silicon (Si) was performed by tetramethyl ammonium hydroxide (TMAH). The transverse piezoelectric coefficient d 31 of the ZnO film, obtained from the deflection of the cantilever with influence of applied voltage, was calculated as 3.32 pC/N. The observed dynamic characterization of the novel piezoelectric microcantilever had linear response with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 39 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…For illustration, based on studies of Ref [ 43 ], the value of E for cadmium selenide (CdSe) is calculated as an average value and E is reported as ~79.233 GPa, so this average value is very far from the standard E value of CdSe that is reported in Ref [ 44 , 45 ]. The E value for zinc oxide (ZnO) through the USDM model is reported as~130 GPa and this value is different from other studies of E ZnO related to this material such as Ref [ 46 , 47 ]. In another study, the USDM model was used for yttrium oxide (Y 2 O 3 ) [ 48 ] and the reported E value did not correspond to other studies such as Ref [ 49 , 50 ].…”
Section: Methodsmentioning
confidence: 58%
“…For illustration, based on studies of Ref [ 43 ], the value of E for cadmium selenide (CdSe) is calculated as an average value and E is reported as ~79.233 GPa, so this average value is very far from the standard E value of CdSe that is reported in Ref [ 44 , 45 ]. The E value for zinc oxide (ZnO) through the USDM model is reported as~130 GPa and this value is different from other studies of E ZnO related to this material such as Ref [ 46 , 47 ]. In another study, the USDM model was used for yttrium oxide (Y 2 O 3 ) [ 48 ] and the reported E value did not correspond to other studies such as Ref [ 49 , 50 ].…”
Section: Methodsmentioning
confidence: 58%
“…Zinc oxide (ZnO) is a promising n-type semiconductor material that is used in a wide range of applications, such as gas detection [1,2,3,4], dye-sensitized solar cells [5,6,7], antibacterial surface coatings [8], light-emitting diodes (LEDs) [9,10], nanopower generators [11], ultraviolet (UV) detection [12,13,14,15], and photocatalytic applications [16,17,18]. ZnO nanostructures have a direct wide band gap (3.37 eV) [19], chemical stability [20], optical [21], piezoelectric [22,23,24], and electrical [25] properties. Additionally, ZnO possesses piezoelectric properties and self-carrier generation when tensile strain force is applied or substrates are bent [26].…”
Section: Introductionmentioning
confidence: 99%
“…Different methods of fabricating piezoelectric materials [11,12,13] lead to the variation of the properties of the device itself. This research article has utilized novel piezoelectric films integrated in the design of a microresonator.…”
Section: Introductionmentioning
confidence: 99%